A dimeric fluorescent protein yields a bright, red-shifted GEVI capable of population signals in brain slice. Issue 1 (December 2018) - Yi, Bumjun; Kang, Bok; Lee, Sungmoo; Braubach, Sophie; Baker, Bradley
Abstract A bright, red-shifted Genetically Encoded Voltage Indicator (GEVI) was developed using a modified version of the fluorescent protein, tdTomato. Dimerization of the fluorescent domain for ArcLight-type GEVIs has been shown to affect the signal size of the voltage-dependent optical signal. For red-shifted GEVI development, tdTomato was split fusing a single dTomato chromophore to the voltage sensing domain. Optimization of the amino acid length and charge composition of the linker region between the voltage sensing domain and the fluorescent protein resulted in a probe that is an order of magnitude brighter than FlicR1 at a resting potential of −70 mV and exhibits a ten-fold larger change in fluorescence (ΔF) upon 100 mV depolarization of the plasma membrane in HEK 293 cells. Unlike ArcLight, the introduction of charged residues to the exterior of dTomato did not substantially improve the dynamic range of the optical signal. As a result, this new GEVI, Ilmol, yields a 3-fold improvement in the signal-to-noise ratio compared to FlicR1 despite a smaller fractional change in fluorescence of 4% per 100 mV depolarization of the plasma membrane. Ilmol expresses well in neurons resolving action potentials in neuronal cultures and reporting population signals in mouse hippocampal acute brain slice recordings. Ilmol is the brightest red-shifted GEVI to date enabling imaging with 160-fold less light than Archon1 for primary neuron recordings (50 mW/cm2 versus 8 W/cm2 ) and 600-fold less light than QuasAr2 for mouse brain slice recordings (500 mW/cm2 versus 300 W/cm2 ). This new GEVI uses a distinct mechanism from other approaches, opening an alternate engineering path to improve sensitivity and speed.